The role of mangrove forests in socio-economic adaptation to coastal morphological changes: Community-based strategies for shoreline shifts and environmental degradation - Pratiwi, Dianita (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The northern coast of Java, especially Demak Regency, is highly vulnerable to natural disasters and human-induced shoreline changes, leading to environmental degradation and direct impacts on local communities. Previous studies have not fully addressed the effects on populations or adaptation strategies. This study aims to assess the effects of shoreline changes on ecosystems and communities while identifying community-based adaptation strategies. Methods: A literature review was conducted, analyzing recent academic articles on shoreline changes and community adaptations. Data were selected based on relevance and analyzed qualitatively to explore the relationship between coastal changes and adaptation strategies. Findings: Shoreline changes are the primary driver of vulnerability in Demak, correlating with mangrove decline. Communities adapt by relying on mangrove ecosystems and implementing socio-economic and structural adjustments to cope with environmental shifts. Conclusion: Shoreline changes significantly affect coastal environments and local communities, necessitating integrated adaptation strategies. Novelty/Originality of this article: This study highlights the relationship between shoreline changes and community adaptations, emphasizing the critical role of mangroves in socio-ecological resilience.